PEMETAAN WILAYAH JELAJAH BABI HUTAN (SUS SCROFA) DI KAWASAN PERBUKITAN BATU BASA - Ifan Wahyudi; Ratna Wilis (JURNAL BUANA, 2022)
Batu Basa village is an agricultural area whose forest area is directly with hilly areas where the area is a natural habitat for boars, so this has resulted in conflicts between forest roaming and agricultural areas. This study aims to 1) Find out how the wild boar ranges in Batu Basa village. 2) How is the conflict zone of the boars attack on the use of agricultural land in Batu Basa village. The method used is Using the Kernel Density Method to determine the range of wild boars based on the density level of the sign of the presence of wild boars and overlaying them with land use maps to obtain conflict zones. The results of this study indicate that the range of the wild boar's home range to the agricultural cultivation area covers a wide area.